Sistem Pengelolaan Piutang Pada PT. Human Resources Provider Menggunakan Metode Analisis Aging Schedule dan Simple Additive Weighting - Parwita, Wayan Gede Suka; Ardini, I Gusti Ayu Ari (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
Human Resources Provider as known as HR Pro is one of outsourcing company. HR Pro provide man power solutions to Human Resources Department at your company. Term of payment between HR Pro and the client are using cash advance payment or charged after payroll process done. Payment system like this can affect to cash flow because almost 90% of company revenue established as receivable in advance. The aim of this research are given solutions to help finance staff for manage account receivable. Account receivables will be sorted from highest to lowest value’s from the results of the calculation aging schedule and simple additive weighting method. This system is using three criterion calculation are receivable values (40%), account receivable aging (35%), number of employee (25%) and finally can give visual appereance in the form of the best solutions using aging schedule and simple additive weighting method. The results of this research are finance staff can manage account receivable easily and the company can make decision quickly for clients who do not pay the invoices based on term of payment.